Developing students’ mastery on adjective using a systemic approach - Mallombasi; Mansur Akil; Iskandar (International Journal of Humanities and Innovation (IJHI), 2018)
This study aimed to investigate the effectiveness of the systemic approach to develop students’ mastery of adjective. The limitations of adjective mastery in this research were the kind, the use, the form, and the order. This research employed a quasiexperimental design with the non-equivalent control group. Sixty-two students in a private university are majoring in English Education chosen from two classes that were divided into two groups, namely experimental and control group. The experimental group was taught by using a systemic approach, while the control group was taught by using lecturing method. The instruments of this research were adjective tests. The data of the experimental group experienced improvement in their mastery of adjective in terms of kind, use, form, and order indicated by the posttest mean score of experimental groups (75.40) that was higher than the posttest mean score of control group (54.6) and the t-test value which was higher than the t-table value (12.991 > 1.671). Furthermore, the researchers found that the element of adjective which experienced most significant development happened on the order. The result of this research indicated that there was significant development between experimental and control class. It means that a systemic approach that was applied in the experimental group could develop the students’ mastery of adjective. Thus, it was concluded that the systemic approach was effective to develop students’ mastery of adjective.